1992
DOI: 10.1021/jm00094a004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of the platelet aggregation inhibitory activity of carbamoylpiperidines

Abstract: A series of alpha,alpha'-bis[3-(N,N-dialkylcarbamoyl)piperidino]-p- xylenes were synthesized and tested for their inhibitory activity on ADP-induced aggregation of human platelets. A parabolic curve was obtained when log 1/C (activity) was plotted against log P (octanol/water partition coefficient). Using this as a model, a new analogue, alpha,alpha'-bis-[3-(N-methyl-N-butylcarbamoyl)piperidino]-p-xylen e (3g), was synthesized with a predicted IC50 of 25 microM. When this compound was subsequently evaluated, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In a preliminary analysis of the relationship between activity and lipophilicity (Altomare et al 2000), we observed that the activity of THPPs increased with increasing lipophilicity, up to a log P value of around 2, beyond which it remained quite constant. This was interpreted as a possible signal of a nonlinear (parabolic or bilinear) dependence of the antiplatelet activity on the lipophilicity, as had been demonstrated in a number of antiplatelet series (Feng et al 1992;Tanaka et al 1994Tanaka et al , 1996. We investigated the partitioning properties of all the derivatives by measuring polycratic capacity factors log k 0 w in RP-HPLC (Altomare et al 1993(Altomare et al , 1994, and comparing them with the octanol±water partition coefficients calculated with the Clog P software.…”
Section: Resultsmentioning
confidence: 73%
“…In a preliminary analysis of the relationship between activity and lipophilicity (Altomare et al 2000), we observed that the activity of THPPs increased with increasing lipophilicity, up to a log P value of around 2, beyond which it remained quite constant. This was interpreted as a possible signal of a nonlinear (parabolic or bilinear) dependence of the antiplatelet activity on the lipophilicity, as had been demonstrated in a number of antiplatelet series (Feng et al 1992;Tanaka et al 1994Tanaka et al , 1996. We investigated the partitioning properties of all the derivatives by measuring polycratic capacity factors log k 0 w in RP-HPLC (Altomare et al 1993(Altomare et al , 1994, and comparing them with the octanol±water partition coefficients calculated with the Clog P software.…”
Section: Resultsmentioning
confidence: 73%
“…Prothrombin is a 72 kDa vitamin K-dependent glycoprotein formed in the liver, 6 it’s a precursor of the serine protease thrombin and play a significant role in the process of hemostasis and thrombosis. 7 Prothrombin gene mutation G20210A is a common prothrombotic single-nucleotide polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the levels of IP 3 and of cytosolic Ca 2? concentrations, necessary for myosin phosphorylation and subsequent platelet activation, are reduced (Youssef and Al-Shafie, 1998;Heath et al, 2004;Feng et al, 1992;Dillingham et al, 1989). Phospholipases A 2 (PLA 2 s) catalyze the hydrolysis of glycerol-phospholipids at the sn-2 position and generate free fatty acids and lysophospholipids (Slotboom et al, 1982).…”
Section: Introductionmentioning
confidence: 99%